Duplication of NRAMP3 Gene in Poplars Generated Two Homologous Transporters with Distinct Functions. (14th June 2022) - Pottier, Mathieu; Le Thi, Van Anh; Primard-Brisset, Catherine; Marion, Jessica; Wolf Bianchi, Michele; Victor, Cindy; Déjardin, Annabelle; Pilate, Gilles; Thomine, Sébastien
Abstract: Transition metals are essential for a wealth of metabolic reactions, but their concentrations need to be tightly controlled across cells and cell compartments, as metal excess or imbalance has deleterious effects. Metal homeostasis is achieved by a combination of metal transport across membranes and metal binding to a variety of molecules. Gene duplication is a key process in evolution, as the emergence of advantageous mutations on one of the copies can confer a new function. Here, we report that the poplar genome contains two paralogues encoding NRAMP3 metal transporters localized in tandem. All Populus species analyzed had two copies of NRAMP3, whereas only one could be identified in Salix species indicating that duplication occurred when the two genera separated. Both copies are under purifying selection and encode functional transporters, as shown by expression in the yeast heterologous expression system. However, genetic complementation revealed that only one of the paralogues has retained the original function in the release of metals stored in the vacuole previously characterized in Arabidopsis thaliana . Confocal imaging showed that the other copy has acquired a distinct localization to the Trans-Golgi Network (TGN). Expression in poplar suggested that the copy of NRAMP3 localized on the TGN has a novel function in the control of cell-to-cell transport of manganese. This work provides a clear case of neofunctionalization through a change in the subcellular localization of a metal transporter as well as evidence for the involvement of the secretory pathway in the cell-to-cell transport of manganese.